Analysis of Structural Changes and Leading Sectors in West Tanjung Jabung Regency - Situmorang, Doan Yoseptian; Udjianto, Didit Welly (Journal of International Conference Proceedings, 2023)
This study aims to determine the leading sectors and potential sectors to be developed and analyze structural changes in West Tanjung Jabung Regency. The methods used in this research are Location Quotient (LQ) and Shift Share Analysis. The data in this study are secondary data in the form of time series data from the Gross Regional Domestic Product (GRDP) of West Tanjung Jabung Regency and Jambi Province obtained from the Central Bureau of Statistics. The researcher found that structural changes occurred in West Tanjung Jabung Regency. This transformation is characterized by the development of the distribution of the industrial sector and services to the GRDP. The results of the Location Quotient (LQ) and Shift Share analysis show that the mining and quarrying sector (B), the manufacturing sector (C) and the company services sector (M, N) are potential basic or leading sectors to be developed in West Tanjung Jabung District. Other sectors that are mainstay sectors such as the agriculture, forestry, and fisheries sector (A), the electricity and gas procurement sector (D), the construction sector (F) and the information and communication sector (J) do not rule out the possibility of being developed into leading sectors because they have competitive advantages and fast growth.